Single breath‐hold 3D cardiac T1 mapping using through‐time spiral GRAPPA. (10th April 2018) - Chen, Yong; Lo, Wei‐Ching; Hamilton, Jesse I.; Barkauskas, Kestutis; Saybasili, Haris; Wright, Katherine L.; Batesole, Joshua; Griswold, Mark A.; Gulani, Vikas; Seiberlich, Nicole
Abstract : The quantification of cardiac T 1 relaxation time holds great potential for the detection of various cardiac diseases. However, as a result of both cardiac and respiratory motion, only one two‐dimensional T 1 map can be acquired in one breath‐hold with most current techniques, which limits its application for whole heart evaluation in routine clinical practice. In this study, an electrocardiogram (ECG)‐triggered three‐dimensional Look–Locker method was developed for cardiac T 1 measurement. Fast three‐dimensional data acquisition was achieved with a spoiled gradient‐echo sequence in combination with a stack‐of‐spirals trajectory and through‐time non‐Cartesian generalized autocalibrating partially parallel acquisition (GRAPPA) acceleration. The effects of different magnetic resonance parameters on T 1 quantification with the proposed technique were first examined by simulating data acquisition and T 1 map reconstruction using Bloch equation simulations. Accuracy was evaluated in studies with both phantoms and healthy subjects. These results showed that there was close agreement between the proposed technique and the reference method for a large range of T 1 values in phantom experiments. In vivo studies further demonstrated that rapid cardiac T 1 mapping for 12 three‐dimensional partitions (spatial resolution, 2 × 2 × 8 mm 3 ) could be achieved in a single breath‐hold of ~12 s. The mean T 1 values of myocardial tissue and blood obtained from normal volunteers at 3 T were 1311 ± 66 and 1890 ± 159 ms, respectively. In conclusion, a three‐dimensional T 1 mapping technique was developed using a non‐Cartesian parallel imaging method, which enables fast and accurate T 1 mapping of cardiac tissues in a single short breath‐hold. Abstract : In this study, a three‐dimensional (3D) cardiac T 1 mapping technique was developed using a spoiled gradient‐echo sequence in combination with a stack‐of‐spirals trajectory and through‐time non‐Cartesian generalized autocalibrating partially parallel acquisition (GRAPPA) acceleration. The method was evaluated with both phantom experiments and human studies, and the in vivo results demonstrate that rapid cardiac T 1 mapping for 12 3D partitions (spatial resolution, 2 × 2 × 8 mm 3 ) can be achieved in a single breath‐hold of ~12 s.